Individualismo interativo: um ensaio sobre o individualismo metodológico de Hayek - Kerstenetzky, Celia Lessa (Estudos Econômicos (São Paulo), 2007)
The main purpose of this paper is to identify the elements for a new kind of methodological individualism - 'interactive individualism' - in Friedrich Hayek's work. This departs from conventional rational choice oriented ideas of methodological individualism in two mains respects. The first has to do with turning the knowledge conditions a problem in its own right, to be sorted out in the process of understanding the social coordination. The second refers to the very unit of analysis which cannot be isolated individuals, taken as given, but 'interacting individuals' instead.